2015
DOI: 10.3892/ol.2015.3110
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in the ω-3 long chain polyunsaturated fatty acid-induced death of lung cancer A549 cells

Abstract: Abstract. The present study identified that ω-3 long chain polyunsaturated fatty acids (ω-3 PUFAs), docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) demonstrate anti-proliferative effects in lung cancer A549 cells. MTS and cytotoxicity assays were conducted to confirm that ω-3 PUFAs induced cell death. Autophagy-associated gene and signaling pathways were also detected. Microtubule-associated protein light chain 3 (LC3) expression was found to be increased subsequent to treatment with DHA and EPA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…The findings of this work outline other ones from Ramos Bueno et al [24], who demonstrated that unspecific oil-derived ARASCO ®and DHASCO ® -MAG induced noticeable in vitro antitumor activity on HT-29 cells. Previous studies demonstrated that DHA significantly decreases cancer cells proliferation [28]; while Pompeia et al [12] found dose-and time-dependent ARA-induced cytotoxicity in leukocytes, i.e., ARA at 10-400 µM induced apoptosis, while at concentrations above 400 µM the noted effect was necrosis. Several studies have discussed the relationship between FAs and mitochondrial permeability transition.…”
Section: Discussionmentioning
confidence: 92%
“…The findings of this work outline other ones from Ramos Bueno et al [24], who demonstrated that unspecific oil-derived ARASCO ®and DHASCO ® -MAG induced noticeable in vitro antitumor activity on HT-29 cells. Previous studies demonstrated that DHA significantly decreases cancer cells proliferation [28]; while Pompeia et al [12] found dose-and time-dependent ARA-induced cytotoxicity in leukocytes, i.e., ARA at 10-400 µM induced apoptosis, while at concentrations above 400 µM the noted effect was necrosis. Several studies have discussed the relationship between FAs and mitochondrial permeability transition.…”
Section: Discussionmentioning
confidence: 92%
“…In response to environmental stresses (e.g., nutrient starvation, hypoxia, infections), autophagy is upregulated to provide the energy supply needed for cell survival and repair [28], and recent studies have shown that the induction of autophagy facilitates cancer cell resistance to Rp-induced apoptosis [29]. Previous studies [19,30]. Thus, we determined whether autophagy plays a key role in the synergistic effects caused by ω-3 PUFA+Rp combination treatment.…”
Section: Combination Treatment Of Rp and ω-3 Pufas Blocks Autophagic mentioning
confidence: 99%
“…Autophagy plays a dual role in cell survival. (22) We showed that inhibition of autophagy further enhanced cell death, suggesting a cytoprotective function for DHA-induced activation of autophagy. By blocking the autophagy pathway using 3-MA and reducing DHA-induced cancer death, we concluded that the DHA effect against tumour cells was mediated through the autophagy pathway.…”
Section: Discussionmentioning
confidence: 75%